(untitled) (Research, Society and Development, 2022)
The cultivation of vegetables in Brazil employs a low technological level in the fertilization system, where macronutrients are prioritized and micronutrients are rarely provided. In this context, the objective was to evaluate the behavior of different sources of boron applied in association with fulvic acids via the soil in the culture of curly lettuce. The experiment was installed in the municipality of Campestre MG, from 09/10/2022 to 10/19/2022. The statistical design used was in randomized blocks with 10 treatments and 4 repetitions, making up 40 experimental units, in a 2 x 5 factorial system (presence and absence of fulvic acids in 4 sources of boron and a control). At 39 days after transplanting, the plants were harvested and the parameters of fresh mass of the aerial part, dry mass of the aerial part, fresh mass of the root, dry mass of the root and stem diameter were evaluated. The collected data were submitted to ANAVA and the Scott - Knott test at 5% significance level. For the variables fresh mass of shoots, dry mass of shoots and stem diameter, all sources of boron were the same and did not differ from the control, regardless of whether they were applied alone or associated with fulvic acids, the same occurring in the treatments where it was applied. fulvic acids alone. In the variables root fresh mass and root dry mass, there was a significant interaction between the sources of boron, boric acid and ulexite, when associated with fulvic acids, being superior to the other treatments.